Turning East: Design Research in China in a Global Context. (1st November 2018) - Fraser, Murray
Abstract : What are the defining qualities of China's current homegrown architectural pioneers, and how might they next evolve?Murray Fraser, Professor of Architecture and Global Culture and Vice‐Dean of Research at the Bartlett School of Architecture, University College London, charts the background of design research from its Western roots, and investigates how recent generations of Chinese architects have been taking it in a new direction – from Wang Shu and Lu Wenyu's Amateur Architecture Studio to Atelier Deshaus, Atelier Archmixing and TAO (Trace Architecture Office).